Dynamical particle ratio fluctuations in Au + Au interaction at Elab = 30 A GeV using transport models. (10th November 2021) - Ghosh, S; Pal, I; Thakur, J; Mukhopadhyay, A; Mali, P
Abstract: We present a simulation study on the dynamical fluctuations of conserved charges in a baryon-rich environment that is expected to be created in high-energy nucleus–nucleus ( AB ) collisions. Microscopic transport models like the ultra-relativistic quantum molecular dynamics and a multi-phase transport model are used to generate Au + Au collision events at an incident beam energy of 30 A GeV in the laboratory system. We investigate the centrality and rapidity window size dependence of the event-by-event (e-by-e) fluctuations of the multiplicity ratios of particles belonging to different species. It is observed that e-by-e dynamical fluctuations in the K / π, K / p and π / p ratios diminish with increasing centrality. Our results in this regard indicate that an AB collision can not be viewed as a mere superposition of many incoherent nucleon–nucleon ( NN ) collisions. Similarly, due to diffusion process the dynamical fluctuations get diluted with increasing window size of rapidity. The simulation results in general could be interpreted in terms of conventional mechanisms of particle production like resonance decays. Our simulation based analysis provides a useful reference baseline to the compressed baryonic matter experiment to be held at the Facility for Antiproton and Ion Research (FAIR).